METHODS OF CONTENTS CURATOR - V. Kukharenko (Kherson State University, 2013)
Content curated - a new activity (started in 2008) qualified network users with process large amounts of information to represent her social network users. To prepare content curators developed 7 weeks distance course, which examines the functions, methods and tools curator. Courses showed a significant relationship success learning on the availability of advanced personal learning environment and the ability to process and analyze information.